Modification of the Optical Properties of Polyvinyl Alcohol through Incorporating Cu2O Nanoparticles Prepared by Laser Ablation - Othman, Chro H.; Sabri, Mohammed F. M.; Ramadan , Simko O. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
A focused, high‐intensity pulsed laser ablated 99.9% - pure copper targets submerged in deionized water and in Polyvinyl alcohol (PVA) solution, respectively, was utilized to produce Cu2O nanoparticles (NPs). Nano-plasmonic cuprous oxide was incorporated using the nanosecond Nd: YAG pulsed laser ablation in liquids technique, which advances the physiochemical characteristics of Cu2O/PVA nanocomposite. Optical characterization was carried out for the induced Cu2O NPs and Cu2O/PVA nanocomposites with six different mass concentrations of Cu2O. The concentrations of the Cu2O NPs were 0.007, 0.017, 0.027, 0.04, 0.047, and 0.057 mg/mL in the PVA matrix. X-ray diffraction confirms that copper ions were reduced to form crystalline Cu2O NPs. Furthermore, DLS showed the presence of NP agglomeration, which revealed polydispersity of Cu2O NPs. The band gap of pristine PVA, determined from Tauc plots, was 5.00 eV. The optical band gap decreased progressively with increasing mass concentration of Cu2O NPs. This band-gap reduction is attributed to changes in the PVA electronic structure caused by incorporated Cu2O NPs. A distinctive feature of this work is the use of pulsed-laser ablation in liquid to generate plasmonic Cu2O NPs and incorporate them in situ into PVA at room temperature in a single step; NP concentration was precisely controlled by the number of laser pulses.